The need to build policy literacy into climate science education. (29th December 2016) - Selin, Noelle E.; Stokes, Leah C.; Susskind, Lawrence E.
Abstract : An increased focus on 'policy literacy' for climate scientists, parallel to 'science literacy' for the public, is a critical need in closing the science–society gap in addressing climate mitigation. We define policy literacy as the knowledge and understanding of societal and decision‐making contexts required for conducting and communicating scientific research in ways that contribute to societal well‐being. We argue that current graduate education for climate scientists falls short in providing policy literacy. We identify resources and propose approaches to remedy this, arguing that policy literacy education needs to be mainstreamed into climate science curricula. Based on our experience training science students in global environmental policy, we propose that policy literacy modules be developed for application in climate science curricula, including simulations, case studies, or hands‐on policy experiences. The most effective policy literacy modules on climate change will be hands‐on, comprehensive, and embedded into scientific education. WIREs Clim Change 2017, 8:e455. doi: 10.1002/wcc.455 This article is categorized under: The Carbon Economy and Climate Mitigation > Policies, Instruments, Lifestyles, Behavior Social Status of Climate Change Knowledge > Knowledge and Practice